The Injury/Illness Performance Project (IIPP): A Novel Epidemiological Approach for Recording the Consequences of Sports Injuries and Illnesses. (27th November 2013) - Palmer-Green, Debbie; Fuller, Colin; Jaques, Rod; Hunter, Glenn
Abstract : Background . Describing the frequency, severity, and causes of sports injuries and illnesses reliably is important for quantifying the risk to athletes and providing direction for prevention initiatives. Methods . Time-loss and/or medical-attention definitions have long been used in sports injury/illness epidemiology research, but the limitations to these definitions mean that some events are incorrectly classified or omitted completely, where athletes continue to train and compete at high levels but experience restrictions in their performance. Introducing a graded definition of performance-restriction may provide a solution to this issue. Results . Results from the Great Britain injury/illness performance project (IIPP) are presented using a performance-restriction adaptation of the accepted surveillance consensus methodologies. The IIPP involved 322 Olympic athletes (males: 172; female: 150) from 10 Great Britain Olympic sports between September 2009 and August 2012. Of all injuries (n = 565 ), 216 were classified as causing time-loss, 346 as causing performance-restriction, and 3 were unclassified. For athlete illnesses (n = 378 ), the majority (P < 0.01 ) resulted in time-loss (270) compared with performance-restriction (101) (7 unclassified). Conclusions . Successful implementation of prevention strategies relies on the correct characterisation of injury/illness risk factors. Including a performance-restriction classification could provide a deeper understanding of injuries/illnesses and better informed prevention initiatives.